ANALISIS KEBUTUHAN LKM UNTUK MENDUKUNG PENINGKATAN LITERASI SAINS PADA PEMBELAJARAN BIOLOGI MURID SMA/MA - Chelvanni Ariati; Lufri (Jurnal Biogenerasi, 2026)
Scientific literacy is an essential twenty-first century skill that supports students in thinking critically and understanding scientific phenomena in everyday life. However, the level of scientific literacy among Indonesian students remains relatively low. This study aimed to analyze the need for Student Worksheets to support the improvement of scientific literacy in biology learning for eleventh-grade senior high school students. This research employed a descriptive method with data collected through student observation questionnaires, scientific literacy questionnaires, biology teacher interviews, and analysis of student’s biology test scores. The results indicate that although student questionnaire responses suggested moderate to high levels of scientific literacy, interview findings and academic performance data revealed that students’ actual scientific literacy was still low. Therefore, the development of scientific literacy-oriented worksheets is needed to enhance biology learning and scientific literacy effectiveness.